Polymer modified carbon nanotube cement mortar as well as preparation method and application thereof

Through polymer-modified carbon nanotube cement mortar, the weak interaction between polymer and carbon nanotubes and ultrasonic dispersion technology are used to solve the problem of uneven dispersion of carbon nanotubes in cement mortar, and the mechanical properties and dispersion of the mortar are improved. The effect reduces the use of admixtures and achieves efficient mechanical properties improvement.

CN119219384APending Publication Date: 2024-12-31TONGJI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411370453.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, carbon nanotubes are dispersed unevenly in the cement mortar, resulting in a decrease in the mechanical properties of the cement mortar, and often need to add dispersants, which is complicated in the preparation steps and high in cost.

Method used

The cement mortar of polymer modified carbon nanotubes is used to adsorb carbon nanotubes on the surface of polymer particles through the weak interaction between polymer and carbon nanotubes, and the nanoscale polymer particles play a steric hindering effect. Achieve good dispersion of carbon nanotubes, and improve the compressive strength and toughness of the mortar through ultrasonic dispersion treatment.

Benefits of technology

Without adding dispersant, good dispersion of carbon nanotubes in the mortar is achieved, the flexural strength and folding pressure ratio of cement mortar are improved, the impact of admixtures on performance is reduced, and the preparation process is simple and the cost is low. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219384A_ABST
    Figure CN119219384A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to polymer modified carbon nanotube cement mortar as well as a preparation method and application thereof. The cement mortar is prepared from the following components in parts by weight: 30 to 60 parts of cement, 90 to 180 parts of fine aggregate, 3 to 6 parts of polymer, 0.015 to 0.09 part of carbon nano tube and 10 to 30 parts of water. The preparation method comprises the following steps: mixing the polymer with the water, adding the carbon nanotubes into the mixture, dispersing, adding the uniformly mixed cement and fine aggregate, and stirring to obtain the cement mortar. Compared with the prior art, the cement mortar disclosed by the invention has a good dispersion effect, the prepared mortar has higher flexural strength and flexural compression ratio, the flexural strength in 28 days can be controlled between 10 and 13MPa, and the flexural compression ratio is improved by 18 to 58 percent compared with the flexural compression ratio of the carbon nano tube cement mortar without polymer modification; the method is suitable for repairing various concrete structures or filling joints of concrete members.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and specifically relates to a polymer modified carbon nanotube cement mortar and a preparation method and application thereof. Background Art

[0002] Cement-based materials are the most widely used building materials in the current construction industry. With the continuous improvement of urbanization, the demand for cement-based materials is growing. In order to reduce the amount of cement-based materials used, cement-based materials are developing towards high strength, high toughness and high durability. In order to improve these properties of cement-based materials, adding carbon nanotubes to them is one of the commonly used methods.

[0003] The dispersibility of carbon nanotubes is a key factor affecting the performance of nanocomposites. Due to the high aspect ratio of carbon nanotubes and the influence of intermolecular van der Waals forces, carbon nanotubes tend to agglomerate and precipitate. Uneven dispersion of carbon nanotubes in cement mortar will affect the reinforcement effect and sometimes even reduce the mechanical properties of cement mortar. In order to achieve a good dispersion effect of carbon nanotubes in cement mortar, a combination of physical dispersion (ultrasonic dispersion, high-speed shear dispersion, etc.) and chemical dispersion (surface modification, dispersant, etc.) is usually adopted. Dispersant combined with ultrasonic treatment is a commonly used dispersion method.

[0004] However, dispersants are usually surfactants, which act as air entrainment in cement materials, resulting in increased porosity, thereby reducing the mechanical properties of cement mortar. In addition, even if carbon nanotubes are well dispersed in an aqueous solution containing a dispersant, they will aggregate in a geometrically dependent manner in cement mortar. This aggregation is mainly because the particle size inside the cement mortar is much larger than the distance between carbon nanotubes, which cannot play a steric hindrance role, so carbon nanotubes aggregate.

[0005] Patent CN109734384A discloses a modified carbon nanotube reinforced cement-based composite slurry and a preparation method thereof, patent CN113292269A discloses a preparation method of carbon nanotube cement mortar that prevents reagglomeration, and patent CN101239800A discloses a carbon nanotube reinforced cement-based composite material and a preparation method thereof. The above dispersion treatments of carbon nanotubes in cement mortar all require the addition of dispersants, or complex dispersion operations on the carbon nanotubes, and the preparation steps are complicated and the required cost is high. Summary of the invention

[0006] The purpose of the present invention is to provide a polymer-modified carbon nanotube cement mortar and its preparation method and application in order to solve at least one of the above-mentioned problems, so as to solve the problem of uneven dispersion of carbon nanotubes in cement mortar in the prior art, achieve a good dispersion effect of carbon nanotubes in cement mortar, and improve the mechanical properties of cement mortar.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] One of the technical solutions of the present invention is to provide a polymer modified carbon nanotube cement mortar, which comprises, by weight, 30-60 parts of cement, 90-180 parts of fine aggregate, 3-6 parts of polymer, 0.015-0.09 parts of carbon nanotubes and 10-30 parts of water.

[0009] Furthermore, in parts by weight, the cement mortar includes 50 parts of cement, 150 parts of fine aggregate, 5 parts of polymer, 0.075 parts of carbon nanotubes and 22.5 parts of water.

[0010] Furthermore, the polymer includes any one of ethylene-vinyl acetate copolymer, styrene-acrylate copolymer and butadiene-styrene copolymer.

[0011] Furthermore, the polymer exists in the form of an emulsion.

[0012] Furthermore, the mass fraction of the added water is related to the solid content of the polymer emulsion, and the mass fraction of the added water is the sum of the mass fraction of water in the polymer emulsion and the mass fraction of water actually added.

[0013] Furthermore, the cement is early strength silicate cement.

[0014] Furthermore, the early strength silicate cement includes any one of P·I42.5R grade cement, P·I52.5R grade cement, P·II42.5R grade cement and P·II52.5R grade cement.

[0015] Furthermore, the fine aggregate includes one or both of river sand and machine-made sand.

[0016] Furthermore, the carbon nanotubes include any one of carboxylated carbon nanotubes and hydroxylated carbon nanotubes.

[0017] The second technical solution of the present invention is to provide a method for preparing the polymer modified carbon nanotube cement mortar as mentioned above, characterized in that the method comprises: mixing the polymer with water, adding carbon nanotubes thereto, after dispersion treatment, adding uniformly mixed cement and fine aggregate, and stirring to obtain the cement mortar.

[0018] Furthermore, the polymer is mixed with water to prepare a polymer solution.

[0019] Furthermore, the dispersion includes any one of ultrasonic dispersion and high-speed shear dispersion.

[0020] Furthermore, the dispersion is ultrasonic dispersion for 10-20 minutes, preferably 15 minutes.

[0021] Furthermore, the dispersed solution is added into a wet mixing pot, and then a dry mixture formed by uniformly mixing cement and fine aggregate is added and mixed to obtain the cement mortar.

[0022] The filling, bridging and nucleation effects of carbon nanotubes are used to improve the compressive strength of the mortar. The weak interaction between the polymer and the carbon nanotubes and the steric hindrance of the polymer particles between the carbon nanotubes are utilized to enable the carbon nanotubes to be fully dispersed inside the mortar. The bridging effect of the polymer film is utilized to further improve the toughness of the carbon nanotube cement mortar.

[0023] The mortar prepared by the present invention has two special properties: 1. Usually, when using carbon nanotubes, a certain amount of dispersant needs to be added to ensure that the carbon nanotubes have a good dispersion effect inside the mortar. The present invention effectively adsorbs the carbon nanotubes on the surface of the polymer particles through the weak interaction between the polymer and the carbon nanotubes without adding a dispersant. In addition, the polymer particles are usually nanometer-sized, which can play a good steric hindrance role and disperse the carbon nanotubes. The above characteristics make the carbon nanotubes have a good dispersion effect inside the mortar, and also reduce the number of admixtures inside the mortar, reducing the impact of admixtures on the performance of the mortar; 2. The addition of dispersant will not further improve the mechanical properties of cement mortar, but will reduce the mechanical properties due to the air entrainment effect. However, the cement mortar prepared by the present invention has excellent mechanical properties. After the polymer is added, the flexural strength and fold-to-compression ratio of the carbon nanotube cement mortar are improved.

[0024] The third technical solution of the present invention is to provide an application of the polymer modified carbon nanotube cement mortar as mentioned above in repairing concrete structures and filling joints of concrete components.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] 1. The present invention effectively adsorbs carbon nanotubes on the surface of polymer particles through weak interaction between polymer and carbon nanotubes without adding any dispersant. In addition, polymer particles are usually nanometer-sized and can play a good steric hindrance role to disperse the carbon nanotubes, which makes the carbon nanotubes have a good dispersion effect inside the mortar, while also reducing the amount of admixtures inside the mortar and reducing the influence of admixtures on the performance of the mortar.

[0027] 2. The cement mortar prepared by the present invention has excellent mechanical properties. The compressive strength of the mortar is improved by the filling, bridging and nucleation effects of carbon nanotubes, and the toughness of the carbon nanotube cement mortar is further improved by the bridging effect of the polymer film. After the polymer is added, the flexural strength and flexural-compression ratio of the carbon nanotube cement mortar are improved. The 28-day flexural strength can be controlled between 10-13MPa, and the flexural-compression ratio is increased by 18%-58% compared with the carbon nanotube cement mortar without polymer modification.

[0028] 3. The preparation process of the cement mortar described in the present invention is simple, and the required materials are few in number, easy to obtain, and easy to implement.

[0029] 4. The cement mortar described in the present invention has low cost and excellent mechanical properties, which is conducive to expanding production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the dispersion effect of hydroxylated carbon nanotubes. DETAILED DESCRIPTION

[0031] The following are some specific examples to illustrate the present invention. These examples are only used to further illustrate the present invention, and are not used to limit the present invention, and do not represent a limitation on the protection scope of the present invention. Some non-essential modifications and adjustments made by others based on the present invention still fall within the protection scope of the present invention.

[0032] Unless otherwise specified, the raw materials or devices used in the following examples are commercially available raw materials or conventional experimental devices.

[0033] Example 1

[0034] A polymer modified carbon nanotube cement mortar comprises, by weight, 50 parts of cement, 150 parts of fine aggregate, 5 parts of polymer, 0.075 parts of carbon nanotubes and 22.5 parts of water.

[0035] The preparation method of the polymer-modified carbon nanotube cement mortar in the above-mentioned embodiment 1 is as follows:

[0036] Step 1: fully mixing ethylene-vinyl acetate copolymer emulsion and water according to a mass ratio to prepare a polymer solution;

[0037] Since the solid content of the ethylene-vinyl acetate emulsion in this embodiment is 56%, the actual mass of the polymer emulsion is weighed to be 8.93 parts. At the same time, the mass of water added is the sum of the mass of water in the polymer emulsion and the mass of water actually added. Therefore, the actual water added is subtracted from the water content in the polymer, and the actual water content added is 18.57 parts.

[0038] Step 2: adding hydroxylated carbon nanotubes to the polymer solution and then dispersing them ultrasonically for 15 minutes to prepare a mixed solution containing polymer-carbon nanotubes;

[0039] Step 3: uniformly mix the P·II52.5R Portland cement and river sand to form a dry mix;

[0040] Step 4: Add the polymer-carbon nanotube mixed solution into a wet stirring pot, and then add the dry mixed material for mixing to obtain the polymer modified carbon nanotube cement mortar.

[0041] Example 2

[0042] A polymer modified carbon nanotube cement mortar comprises, by weight, 50 parts of cement, 150 parts of fine aggregate, 5 parts of polymer, 0.075 parts of carbon nanotubes and 22.5 parts of water.

[0043] The preparation method of the polymer-modified carbon nanotube cement mortar in the above-mentioned embodiment 1 is as follows:

[0044] Step 1: fully mixing the styrene-acrylate copolymer emulsion and water in a mass ratio to prepare a polymer solution;

[0045] Since the solid content of the styrene-acrylate copolymer emulsion in this embodiment is 57%, the actual mass of the polymer emulsion is weighed to be 8.77 parts, and the mass of the water added is the sum of the mass of the water in the polymer emulsion and the mass of the water actually added. Therefore, the actual water added is subtracted from the water content in the polymer, and the actual water added is 18.73 parts;

[0046] Step 2: adding hydroxylated carbon nanotubes to the polymer solution and then dispersing them ultrasonically for 15 minutes to prepare a mixed solution containing polymer-carbon nanotubes;

[0047] Step 3: uniformly mix the P·II52.5R Portland cement and river sand to form a dry mix;

[0048] Step 4: Add the polymer-carbon nanotube mixed solution into a wet stirring pot, and then add the dry mixed material for mixing to obtain the polymer modified carbon nanotube cement mortar.

[0049] Example 3

[0050] A polymer modified carbon nanotube cement mortar comprises, by weight, 50 parts of cement, 150 parts of fine aggregate, 5 parts of polymer, 0.075 parts of carbon nanotubes and 22.5 parts of water.

[0051] The preparation method of the polymer-modified carbon nanotube cement mortar in the above-mentioned embodiment 1 is as follows:

[0052] Step 1: fully mixing a butadiene-styrene copolymer emulsion and water in a mass ratio to prepare a polymer solution;

[0053] Since the solid content of the butadiene-styrene copolymer emulsion in this embodiment is 51%, the actual mass of the polymer emulsion is weighed to be 9.80 parts, and the mass of the water added is the sum of the mass of the water in the polymer emulsion and the mass of the water actually added. Therefore, the actual water added is subtracted from the water content in the polymer, and the actual water added is 17.70 parts;

[0054] Step 2: adding hydroxylated carbon nanotubes to the polymer solution and then dispersing them ultrasonically for 15 minutes to prepare a mixed solution containing polymer-carbon nanotubes;

[0055] Step 3: uniformly mix the P·II52.5R Portland cement and river sand to form a dry mix;

[0056] Step 4: Add the polymer-carbon nanotube mixed solution into a wet stirring pot, and then add the dry mixed material for mixing to obtain the polymer modified carbon nanotube cement mortar.

[0057] Example 4

[0058] A polymer modified carbon nanotube cement mortar comprises, by weight, 50 parts of cement, 150 parts of fine aggregate, 5 parts of polymer, 0.075 parts of carbon nanotubes and 22.5 parts of water.

[0059] The preparation method of the polymer-modified carbon nanotube cement mortar in the above-mentioned embodiment 1 is as follows:

[0060] Step 1: fully mixing ethylene-vinyl acetate copolymer emulsion and water according to a mass ratio to prepare a polymer solution;

[0061] Since the solid content of the ethylene-vinyl acetate emulsion in this embodiment is 56%, the actual mass of the polymer emulsion is weighed to be 8.93 parts. At the same time, the mass of water added is the sum of the mass of water in the polymer emulsion and the mass of water actually added. Therefore, the actual water added is subtracted from the water content in the polymer, and the actual water content added is 18.57 parts.

[0062] Step 2: adding the carboxylated carbon nanotubes to the polymer solution and then dispersing them ultrasonically for 15 minutes to prepare a mixed solution containing polymer-carbon nanotubes;

[0063] Step 3: uniformly mix the P·II52.5R Portland cement and river sand to form a dry mix;

[0064] Step 4: Add the polymer-carbon nanotube mixed solution into a wet stirring pot, and then add the dry mixed material for mixing to obtain the polymer modified carbon nanotube cement mortar.

[0065] Example 5

[0066] A polymer modified carbon nanotube cement mortar comprises, by weight, 50 parts of cement, 150 parts of fine aggregate, 5 parts of polymer, 0.075 parts of carbon nanotubes and 22.5 parts of water.

[0067] The preparation method of the polymer-modified carbon nanotube cement mortar in the above-mentioned embodiment 1 is as follows:

[0068] Step 1: fully mixing ethylene-vinyl acetate copolymer emulsion and water according to a mass ratio to prepare a polymer solution;

[0069] Since the solid content of the ethylene-vinyl acetate emulsion in this embodiment is 56%, the actual mass of the polymer emulsion is weighed to be 8.93 parts. At the same time, the mass of water added is the sum of the mass of water in the polymer emulsion and the mass of water actually added. Therefore, the actual water added is subtracted from the water content in the polymer, and the actual water content added is 18.57 parts.

[0070] Step 2: adding hydroxylated carbon nanotubes to the polymer solution and then dispersing them ultrasonically for 15 minutes to prepare a mixed solution containing polymer-carbon nanotubes;

[0071] Step 3: Evenly mix the P·I52.5R silicate cement and river sand to form a dry mix;

[0072] Step 4: Add the polymer-carbon nanotube mixed solution into a wet stirring pot, and then add the dry mixed material for mixing to obtain the polymer modified carbon nanotube cement mortar.

[0073] Example 6

[0074] A polymer modified carbon nanotube cement mortar comprises, by weight, 50 parts of cement, 150 parts of fine aggregate, 5 parts of polymer, 0.075 parts of carbon nanotubes and 22.5 parts of water.

[0075] The preparation method of the polymer-modified carbon nanotube cement mortar in the above-mentioned embodiment 1 is as follows:

[0076] Step 1: fully mixing ethylene-vinyl acetate copolymer emulsion and water according to a mass ratio to prepare a polymer solution;

[0077] Since the solid content of the ethylene-vinyl acetate emulsion in this embodiment is 56%, the actual mass of the polymer emulsion is weighed to be 8.93 parts. At the same time, the mass of water added is the sum of the mass of water in the polymer emulsion and the mass of water actually added. Therefore, the actual water added is subtracted from the water content in the polymer, and the actual water content added is 18.57 parts.

[0078] Step 2: adding hydroxylated carbon nanotubes to the polymer solution and then dispersing them ultrasonically for 15 minutes to prepare a mixed solution containing polymer-carbon nanotubes;

[0079] Step 3: uniformly mix the P·II52.5R silicate cement and machine-made sand to form a dry mix;

[0080] Step 4: Add the polymer-carbon nanotube mixed solution into a wet stirring pot, and then add the dry mixed material for mixing to obtain the polymer modified carbon nanotube cement mortar.

[0081] Comparative Example 1

[0082] Comparative Example 1 is a carbon nanotube cement mortar without adding polymer.

[0083] A carbon nanotube cement mortar comprises, by weight, 50 parts of cement, 150 parts of fine aggregate, 0.075 parts of carbon nanotubes and 22.5 parts of water.

[0084] Step 1: adding hydroxylated carbon nanotubes to water and dispersing them ultrasonically for 15 minutes to prepare a solution containing carbon nanotubes;

[0085] Step 2: uniformly mix P·II52.5R Portland cement and river sand to form a dry mix;

[0086] Step 3: Add the carbon nanotube solution into a wet mixing pot, and then add the dry mixed material for mixing to obtain the carbon nanotube cement mortar.

[0087] The raw material composition ratios of Examples 1-3 and Blank Example 1 are shown in Table 1:

[0088] Table 1 Raw material components and ratios of Examples 1-6 and Blank Example 1

[0089]

[0090] Then, Examples 1-6 and Comparative Example 1 were tested as follows:

[0091] (1) Evaluation of the dispersion effect of carbon nanotubes: The dispersion effect of hydroxylated carbon nanotubes in a saturated calcium hydroxide solution and a calcium hydroxide solution containing ethylene-vinyl acetate copolymer was evaluated using a UV-visible spectrophotometer:

[0092] The results are as follows Figure 1 As shown, Figure 1 The black line in the middle shows the dispersion effect of hydroxylated carbon nanotubes in saturated calcium hydroxide solution. Figure 1 The green line in the middle shows the dispersion effect of hydroxylated carbon nanotubes in calcium hydroxide solution containing ethylene-vinyl acetate copolymer. Figure 1 It can be seen that carbon nanotubes have a π-π* transition peak at 260nm ( Figure 1 The red dashed line in the middle shows the concentration of carbon nanotubes in the solution. Figure 1 It can be seen that carbon nanotubes have a good dispersion effect in the solution containing ethylene-vinyl acetate copolymer, especially when the solution is left to stand for 30 minutes, the concentration of carbon nanotubes in the solution containing ethylene-vinyl acetate copolymer is significantly higher than that in the control group.

[0093] (2) Evaluation of mechanical properties of cement mortar: Determine the flexural and compressive strengths according to GB / T 17671-1999 (ISO679:1989) “Test method for strength of cement mortar”:

[0094] The mechanical properties of Examples 1-4 are shown in Table 2 below, and the mechanical properties of Examples 5-6 are close to those of Example 1. As can be seen from Table 2, the flexural strength and flexural-compression ratio of the cement mortars prepared in Examples 1-4 are significantly improved compared to the carbon nanotube cement mortar prepared in Comparative Example 1. High-toughness cement mortar is suitable for repairing concrete structures and filling joints.

[0095] Table 2 Mechanical properties of cement mortar of Examples 1-4 and Comparative Example 1

[0096] Test items Example 1 Example 2 Example 3 Example 4 Comparative Example 1 28d compressive strength (MPa) 59.28 47.27 39.9 59.86 59.48 28d flexural strength (MPa) 11.79 12.64 10.13 12.12 9.97 28d fold-compression ratio 0.199 0.267 0.254 0.202 0.168

[0097] In summary, the polymer-modified carbon nanotube cement mortar prepared by the present invention has a good dispersion effect of carbon nanotubes inside the mortar without adding a dispersant. Compared with the carbon nanotube cement mortar, the polymer-modified carbon nanotube cement mortar of the present invention has higher flexural strength and flexural-compression ratio. The 28-day flexural strength can be controlled between 10-13MPa, and the compressive strength can be controlled between 35-60MPa. The flexural-compression ratio is increased by 18%-58% compared with the carbon nanotube cement mortar without adding polymer modification.

[0098] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A polymer-modified carbon nanotube cement mortar, characterized in that: In parts by weight, the cement mortar includes 30-60 parts of cement, 90-180 parts of fine aggregate, 3-6 parts of polymer, 0.015-0.09 parts of carbon nanotubes and 10-30 parts of water.

2. The polymer-modified carbon nanotube cement mortar according to claim 1, characterized in that: In parts by weight, the cement mortar includes 50 parts of cement, 150 parts of fine aggregate, 5 parts of polymer, 0.075 parts of carbon nanotubes and 22.5 parts of water.

3. The polymer-modified carbon nanotube cement mortar according to claim 1, characterized in that: The polymer includes any one of ethylene-vinyl acetate copolymer, styrene-acrylate copolymer and butadiene-styrene copolymer.

4. The polymer-modified carbon nanotube cement mortar according to claim 1, characterized in that: The polymer is present in the form of an emulsion.

5. The polymer-modified carbon nanotube cement mortar according to claim 1, characterized in that: The cement is early strength type silicate cement.

6. The polymer-modified carbon nanotube cement mortar according to claim 5, characterized in that: The early strength silicate cement includes any one of P·I42.5R grade cement, P·I52.5R grade cement, P·II42.5R grade cement and P·II52.5R grade cement.

7. The polymer-modified carbon nanotube cement mortar according to claim 1, characterized in that: The fine aggregate includes one or both of river sand and machine-made sand.

8. The polymer-modified carbon nanotube cement mortar according to claim 1, characterized in that: The carbon nanotubes include any one of carboxylated carbon nanotubes and hydroxylated carbon nanotubes.

9. A method for preparing the polymer-modified carbon nanotube cement mortar as claimed in claim 1, characterized in that: The method comprises: mixing a polymer with water, adding carbon nanotubes thereto, and after dispersion treatment, adding uniformly mixed cement and fine aggregates, and stirring to obtain the cement mortar.

10. Use of the polymer-modified carbon nanotube cement mortar as claimed in claim 1 in repairing concrete structures and filling joints of concrete components.